2020
DOI: 10.1089/can.2019.0098
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Disposition and Metabolic Interactions of Cannabidiol Through CYP3A Inhibition In Vivo in Rats

Abstract: Introduction: Cannabidiol (CBD) is known to affect the pharmacokinetics of other drugs through metabolic inhibition of CYP2C19 and CYP3A4. However, there is a lack of in vivo evidence for such drug interactions. Therefore, we investigated the saturability of CBD metabolism and CBD-drug interactions through inhibition of CYP3A in vivo. Materials and Methods: A nanoemulsion formulation of CBD (CBD-NE) was orally administered to rats at doses of 5, 10, 25, and 50 mg/kg, and plasma concentrations of CBD were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In rats, 24 studies reported anxiety outcomes (Almeida et al, 2013;Espejo-Porras et al, 2013;Gáll et al, 2020;Gazarini et al, 2014;Guimarães et al, 1994;Hložek et al, 2017;Javadi-Paydar et al, 2019;Jurkus et al, 2016;Kajero et al, 2020;Karniol et al, 1974;Lemos et al, 2010;Mahmud et al, 2017;Malone et al, 2009;Martín-González et al, 2018;Moreira et al, 2006;Murkar et al, 2019;O'Brien et al, 2013;Resstel et al, 2006;Rock et al, 2017;Shallcross et al, 2019;Shoval et al, 2016;Song et al, 2016;Stern et al, 2012Stern et al, , 2015 and 10 studies reported only PK outcomes (Cherniakov et al, 2017;Deiana et al, 2012;Feng et al, 2021;Izgelov et al, 2020bIzgelov et al, , 2020cIzgelov et al, , 2020dNagao et al, 2020;Paudel et al, 2010;Xu et al, 2019;Zgair et al, 2016). In one study, both types of outcomes were reported (Hložek et al, 2017).…”
Section: Description Of Studies Included In the Data Synthesismentioning
confidence: 99%
“…In rats, 24 studies reported anxiety outcomes (Almeida et al, 2013;Espejo-Porras et al, 2013;Gáll et al, 2020;Gazarini et al, 2014;Guimarães et al, 1994;Hložek et al, 2017;Javadi-Paydar et al, 2019;Jurkus et al, 2016;Kajero et al, 2020;Karniol et al, 1974;Lemos et al, 2010;Mahmud et al, 2017;Malone et al, 2009;Martín-González et al, 2018;Moreira et al, 2006;Murkar et al, 2019;O'Brien et al, 2013;Resstel et al, 2006;Rock et al, 2017;Shallcross et al, 2019;Shoval et al, 2016;Song et al, 2016;Stern et al, 2012Stern et al, , 2015 and 10 studies reported only PK outcomes (Cherniakov et al, 2017;Deiana et al, 2012;Feng et al, 2021;Izgelov et al, 2020bIzgelov et al, , 2020cIzgelov et al, , 2020dNagao et al, 2020;Paudel et al, 2010;Xu et al, 2019;Zgair et al, 2016). In one study, both types of outcomes were reported (Hložek et al, 2017).…”
Section: Description Of Studies Included In the Data Synthesismentioning
confidence: 99%
“…The double-edged-sword-like pharmacological effects have been confirmed from the phytocannabinoids, which were enriched in the female inflorescence. With the discovery of medicinal uses of cannabidiol (CBD) [ 2 , 3 ] and the development of related drugs in recent years, some countries and regions such as the United States and Canada have implemented Cannabis species legalization policies.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews and research reports in humans and laboratory animals have described the in vivo and in vitro toxicologic effects of CBD-containing hemp extracts at various dosage levels [ 13 , [18] , [19] , [20] , [21] , [22] ]. The authors concluded that these studies generally support the conclusion that CBD-containing hemp extracts are safe for humans inclusive of intermittent chronic use.…”
Section: Introductionmentioning
confidence: 99%